1988
DOI: 10.1152/jappl.1988.65.2.829
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal mucosal blood flow responses to autonomic agonists

Abstract: In lightly anesthetized adult sheep, we determined tracheal mucosal blood flow (Qtr) by measuring the steady-state uptake of dimethyl ether from a tracheal chamber created by an endotracheal tube provided with two cuffs. Qtr normalized for carotid arterial pressure [Qtr(n)] was determined before and after the exposure of the tracheal mucosa to aerosolized phenylephrine (0.25-2.0 mg), isoproterenol (0.05-0.8 mg), and methacholine (2.5-20 mg). The same doses of methacholine were also administered during the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The sympathetic nervous system provides local control of airway blood flow by releasing norepinephrine, which causes vasoconstriction through activation of a 1 -adrenoreceptors on vascular smooth muscle [98][99][100]. The a 1 -adrenergic responsiveness of airway blood flow has been confirmed in vivo, and additionally shown to be potentiated in asthmatics [94].…”
Section: Abnormalities Of Blood Flow Regulationmentioning
confidence: 96%
“…The sympathetic nervous system provides local control of airway blood flow by releasing norepinephrine, which causes vasoconstriction through activation of a 1 -adrenoreceptors on vascular smooth muscle [98][99][100]. The a 1 -adrenergic responsiveness of airway blood flow has been confirmed in vivo, and additionally shown to be potentiated in asthmatics [94].…”
Section: Abnormalities Of Blood Flow Regulationmentioning
confidence: 96%
“…Stimulation of alpha receptors causes vasoconstriction and a decrease in flow 56 and beta-adrenergic agonists cause vasodilatation and an increase in flow. 57,58 Whereas the response of both mucosal and total bronchial blood flow to sympathetic stimulation is well documented, the response of the bronchial circulation to parasympathetic stimulation is less clear. The response of the mucosal circulation may differ from that of Q br ; Scuri et al 12 showed that in anesthetized sheep vagal nerve stimulation and intra-arterial acetylcholine (Ach) both increase Q br , whereas the mucosal circulation appears to lack cholinergic muscarinic responsiveness, showing no increase in blood flow following aerosol administration of Ach.…”
Section: Neurohumoral Factorsmentioning
confidence: 99%
“…By increasing or decreasing the transcription of genes related to a variety of activities [7,[9][10][11][12], these drugs may downregulate several inflammatory and immune effector cell functions, including proliferation of T lymphocytes [13], release of growth factors [14] and arachidonic acid metabolites by monocytes [15], expression of growth factor receptors [16] and of class II molecules by mononuclear cells [17].…”
Section: Introductionmentioning
confidence: 99%